2020
DOI: 10.1039/d0nj03403g
|View full text |Cite
|
Sign up to set email alerts
|

A good-performance glucose sensor fabricated via rationally designing a new cobalt–metal–organic framework precursor

Abstract: A good-performance glucose sensor based on Co3O4 has been firstly synthesized by rational designing a new cobalt-metal-organic framework precursor with structural formula of [Co(Cia)2(bmb)]n (Cia =5-((4-carboxybenzyl)oxy)isophthalic acid, bmb = 1,4-bis(2-methylbenzimidazol-1-ylmethyl)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 43 publications
2
6
0
Order By: Relevance
“…As the calcination temperature increasing from 550 °C to 750 °C, the particles further fused, agglomerated, and large irregular lump morphology could be observed at 750 °C, as shown in Figure 2(C)–Figure 2(E). This phenomena could also be founded in reported literature [25] . The TEM measurement further confirmed the successful preparation of Fe/Fe 3 O 4 @C‐ 650 .…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…As the calcination temperature increasing from 550 °C to 750 °C, the particles further fused, agglomerated, and large irregular lump morphology could be observed at 750 °C, as shown in Figure 2(C)–Figure 2(E). This phenomena could also be founded in reported literature [25] . The TEM measurement further confirmed the successful preparation of Fe/Fe 3 O 4 @C‐ 650 .…”
Section: Resultssupporting
confidence: 87%
“…This phenomena could also ChemistrySelect be founded in reported literature. [25] The TEM measurement further confirmed the successful preparation of Fe/Fe 3 O 4 @C-650 . Figure 2(F) showed the TEM image of Fe/Fe 3 O 4 @C -650.…”
Section: Characterizationssupporting
confidence: 54%
“…Because cobalt contained in LICONPs acts as a catalyst for glucose oxidation, Nafion/LICONPs/LIGF increased the current in the glucose‐containing electrolyte. The possible reaction process for the electrocatalytic oxidation of Co in the LICONPs layer to glucose is proposed as in Equations (1), (2), and : [29] truenormalCnormalo3O4+normalOnormalH-+H2normalO3normalCnormalonormalOnormalOnormalH+normale- truenormalCnormalonormalOnormalOnormalH+normalOnormalH-normalCnormalonormalO2+H2normalO+normale- true2normalCnormalonormalO2+C6H12O6()glucose2normalCnormalonormalOnormalOnormalH+C6H10O6()gluconolactone …”
Section: Resultsmentioning
confidence: 99%
“…Because cobalt contained in LICONPs acts as a catalyst for glucose oxidation, Nafion/LICONPs/LIGF increased the current in the glucosecontaining electrolyte. The possible reaction process for the electrocatalytic oxidation of Co in the LICONPs layer to glucose is proposed as in Equations ( 1), (2), and (3): [29] Co…”
Section: Electrical and Electrochemical Properties Of The Liconps/lig...mentioning
confidence: 99%
“…[4][5][6] Naturally, people look for alternative yet attractive strategy like deploying non-enzymatic glucose sensors due to their lower cost, easy processing and storage, faster response, and long lifespan. It was revealed that various metals in their oxide forms exhibit good electrocatalytic behaviour and could oxidize glucose directly e.g., cobalt, 7 nickel, 8,9 palladium, 10 vanadium, 11 copper, 12 molybdenum 13 etc. Their glucose oxidizing capability makes them potential candidates for selective and accurate detection of glucose present in the solution, or serum in very low concentration.…”
mentioning
confidence: 99%